Lathyrism: has the scenario changed in 2013?. (January 2014) - Mishra, V. N.; Tripathi, C. B.; Kumar, A.; Nandmer, V.; Ansari, A. Z.; Kumar, B.; Chaurasia, R. N.; Joshi, D.
<x content-type="archive" xml:space="preserve">Abstract</x> Lathyrism is now rarely seen as a clinical disease in general, medical or neurology outpatient departments, throughout the world. Eating patterns of seeds of Lathyrus sativus are still prevalent focal points in parts of the world. Question arises, why are we not seeing cases of lathyrism? Is it that the disease has changed its profile, with the changing socioeconomic status of the poor or underdeveloped or moderately developed countries? Is it that the seeds of lathyrus are less toxic now? Is it that the body defence against toxins of lathyrus has genetically modified? To find out answers to these interesting questions, an extensive questionnaire-based sampling was done among 1000 subjects from northern India to identify the human behaviour regarding the knowledge, attitude, and practices (KAPs) for L. sativus. Four clinically suspected cases of Lathyrism were also fully worked up. It was concluded that many areas of India are still being fed with lathyrus seeds, but not many cases have appeared. Many questions have to be answered, as to what has reduced the incidence of lathyrism.